SPH modeling of substance transport in flows with large deformation - Liu, Wanying; Hou, Qingzhi; Lei, Xiaohui; Lian, Jijian; Dang, Jianwu (Frontiers in Environmental Science, 2022)
The velocity field in coastal and oceanic currents is mostly non-uniform, which will result in irregular particle distribution when the fluid is represented by an amount of moving discrete particles as in smoothed particle hydrodynamics (SPH). When the non-uniformity of the flow is big, i.e., with large deformation, the conventional SPH method can hardly solve the associated advection-diffusion process (e.g., substance transport). To accurately simulate the substance transport in flows with large deformation, two types of particle shifting techniques (PSTs) are incorporated into the conventional SPH in this paper. One is based on current particle distance, and the other is based on Fick’s law. In the second type, the repulsive force (RF) term for suppressing the paring instability that occurs in PST is studied and the effect of the kernel function is examined. By introducing a particle disorder measurement, the simulated results of SPH with the two types of PSTs and their modifications are evaluated and the influence of the shifting magnitude is analyzed. The suggestions for how to set reasonable parameters in PSTs are provided by a systematic parametric study. For further illustration, the simulation of the anisotropic diffusion is also examined. To give reliable reference solutions, the high-resolution modified total variation diminishing Lax Friedrichs scheme with superbee limiter (MTVDLF-superbee) with fine mesh is also implemented. The validated Lagrangian particle model with optimized PST is applied to a practical application.